Condition for effective functioning and development of the elite higher education system: elemental and structural balance - Slyusarenko О (Continuing Professional Education: Theory and Practice, 2019)
Adequate understanding of the problematic aspects in functioning of elite higher education and formulation of effective theoretical and conceptual recommendations in order to overcome its disadvantages should be based on key factors that determine the capacity of the educational sphere. First of all, there is a need in a thorough comprehension of the systemic status of education and its functional and instrumental vocation within the mega system of the society and humanity as well. It is necessary to understand the evidence, which for some reasons often is on the periphery of attention not only of the mass consciousness but also of some experts in conceptual educational sphere, namely, education is not an autonomous reality that functions at its discretion; this is the element of socio-cultural and global systems capacity which is largely determined by a coherence and synchronization of its efforts with the needs and opportunities of the mega systems to which it belongs. The essence of the problem and its theoretical and praxeological relevance is that the vast majority of inefficient conceptual recommendations for education as a whole and elite education in particular is caused by imbalances and asymmetry between problematic and propositional formats: thus, partial or segmented propositions a priori are unable to neutralize the systemic weaknesses and on the other hand to provide the systemic status for recommendations generated by the results of comprehension of the educational reality aspects in general appears to be an unprofessional mechanism that provokes deepening and aggravation of crisis symptoms. The contribution of the author is to use proper scientific approach – involving a comprehensive, system analysis to system of elite education to its interpretation in the context of major impacts. An important factor that enhances a systemic mode of system mechanisms is well-known globalization. Its attribute and effect is such a reality within which each local event is greatly influenced by certain developments in other functional segments that simultaneously influences them with a tangible opposite effects. Moreover, the given functional algorithm is inherent not only for global and universal levels; it works quite well as within individual societies and social institutions.